Aesthetic-chemical properties and clinical indications of giomers: literature review - Huss, Ana Beatriz Mori; Hayashi, Ellen Namie; Mistrello, Yasmin Ávila; Kondo, Glen Victor; Bispo, Carina Gisele Costa; Veltrini, Vanessa Cristina (Revista Uningá, 2022)
Giomer is a hybrid restorative material, developed in the 2000s, which presents a combination of characteristics and properties of both composite resin and ionomeric cement, but whose clinical indications are still unclear. The present review aims to evaluate the literature that addresses these indications, as well as the aesthetic and chemical properties, compared to traditional non-hybrid restorative materials. The bibliographic search was carried out in PubMed, LILACS and SciELO databases, from 2016 to 2022. It included articles published in English, Portuguese and Spanish, and used strategies adapted to each database and descriptors compatible with the objective. Publications whose full versions were duplicated and/or unavailable for free access were excluded. From an initial total of 137 articles, 14 were selected. It was observed that there are still doubts about the amount of fluoride released over time and about the possibility of a burst effect, that is, the initial explosion effect that occurs in the first 24 hours and decreases with time, similar to what occurs with glass ionomer cement and not with conventional resins. In the light of the consulted literature, it is possible to conclude that giomers, as well as composite resins, can be widely indicated for restorative procedures, as they have satisfactory resistance and aesthetics, in addition to releasing enough fluoride to prevent caries, making it possible to recharge them from this ion, as in glass ionomer cements.